Avances en el uso de simulaciones computacionales para comprender mejor los efectos biomecánicos del glaucoma - Rosales Medina, Luis Mario; Bazán, I. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The use of computational simulations using the finite element method is a useful tool to observe the effects that intraocular pressure causes on some structures of the eye. Both, the simulations that focus on analyzing the anterior and posterior poles provide data about changes that occur having certain pressure values. Even knowing that the main effects of primary angle glaucoma are palpable in the optic nerve, the usefulness of the results obtained from simulations that focus on studying the cornea or other structures is not ruled out, since these are structures affected since that is where it originates in a glaucoma disease beginning. This review article tries to cover some of the articles focused on computational simulations of the eye and its biomechanical changes due to glaucoma in recent years, as well as to review the considerations that were made in each one to arrive at their respective results.